Distinct Autoimmune Anti-α-Synuclein Antibody Patterns in Multiple System Atrophy and Parkinson’s Disease - Folke, Jonas; Rydbirk, Rasmus; Løkkegaard, Annemette; Salvesen, Lisette; Hejl, Anne-Mette; Starhof, Charlotte; Bech, Sára; Winge, Kristian; Christensen, Søren; Pedersen, Lars Østergaard; Aznar, Susana; Pakkenberg, Bente; et al. (Frontiers in Immunology, 2019)
Aggregation of alpha-synuclein (α-syn) is considered to be the major pathological hallmark and driving force of Multiple System Atrophy (MSA) and Parkinson’s disease (PD). Immune dysfunctions have been associated with both MSA and PD and recently we reported that the levels of natural occurring autoantibodies (NAbs) with high affinity towards α-synuclein are reduced in MSA and PD patients. Here, we aimed to evaluate the plasma immunoglobulin (Ig) composition binding α-syn and other amyloidogenic neuropathological proteins, and to correlate them with disease severity and duration in MSA and PD patients. All participants were recruited from a single neurological unit and the plasma samples were stored for later research at the Bispebjerg Movement Disorder Biobank. All patients were diagnosed according to current consensus criteria. Using multiple variable linear regression analyses, we observed higher levels of anti-α-syn IgG1 and IgG3 NAbs in MSA versus PD, higher levels of anti-α-syn IgG2 NAbs in PD compared to controls, whereas anti-α-syn IgG4 NAbs were reduced in PD compared to MSA and controls. Anti-α-syn IgM levels were decreased in both MSA and PD. Further our data supported that MSA patients’ immune system was affected with reduced IgG1 and IgM global levels compared to PD and controls, with further reduced global IgG2 levels compared to PD. These results suggest distinct autoimmune patterns in MSA and PD. These findings suggest a specific autoimmune physiological mechanism involving responses towards α-syn, differing in neurodegenerative disease with overlapping α-syn pathology.